Recent Publications (Quarterly Journal of Economics, 1967)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 81, Issue 2, May 1967, Pages 353–357, https://doi.org/10.1093/qje/81.2.353 Published: 01 May 1967